Let’s rebuild our gender identities from diversity: an experience from a critical pedagogy standpoint. - Baracaldo Acosta, Rosmelys (2013)
This article derives from the thesis of the authors to opt for the Licenciate degree in the Teaching of Social Studies and Civics. In this work, fundamentals of critical pedagogy were applied to the didactical experience of addressing the topic of “Rebuilding our gender identities”, from a focus on sexual diversity;; in order to raise awareness and critical thinking in the 8th grade Civics classes of the National Virtual High School Marco Tulio site in Guadalupe, San José 2012.